Revision of the genus Trachytedania (Porifera: Poecilosclerida) with a description of Trachytedania ferrolensis sp.nov. from the north-east Atlantic. - Cristobo, F.J; Urgorri, V. (Journal of the Marine Biological Association of the United Kingdom, 2001)
The genus Trachytedania Ridley, 1881 Porifera: Poecilosclerida), includes those tedaniidae sponges characterized by the presence of acanthostyles. To date, only ¢ve species of the genus Trachytedania have been described of which only three actually belong to this genus. Other species described as Tedania could be considered as Trachytedania because of the presence of acanthostyles in their skeletons. Some authors propose retaining Trachytedania as a subgenus of Tedania because of its skeletal structure. In this work, a taxonomic revision and consideration of the validity of the genus is provided. The morphology and anatomy of Trachytedania ferrolensis sp. nov. from the Ria de Ferrol Spain, north-east Atlantic) are described in detail, and the types of the three valid species described as Trachytedania to date: Trachytedania spinata, Trachytedania patagonica and Trachytedania biraphidora are studied. A key to this genus is provided